Exploring AI-Based Learning Tools for Personalized English Learning: Learners' Experiences at English House Language Center - Adam Rahman Arif; Mustakim Mustakim; Hasan Hasan; Musdalifah Musdalifah; Sri Rosmiana (Journal of Excellence in English Language Education, 2026)
Artificial Intelligence (AI)-based learning tools have become increasingly popular in supporting personalized English learning. However, limited research has explored their use in non-formal language learning contexts. This qualitative descriptive study investigates the use of AI-based learning tools to support personalized English learning at English House Language Center. Data were collected through questionnaires, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The study explores how learners use AI-based learning tools, the benefits they experience, and the challenges they encounter. The findings are expected to provide insights into the role of AI in promoting learner autonomy, personalized learning, and flexible English learning while identifying challenges related to technology use and teacher support. This study contributes to the growing literature on AI-assisted English language learning.